2022
DOI: 10.25047/animpro.2022.343
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the growth curve of body weight in Ettawa Crossbred Goats with Logistic and Gompertz mathematical models

Widya Pintaka Bayu Putra,
Tantan Rustandi Wiradarya,
Anwar Efendi Harahap
et al.

Abstract: Ettawa crossbred goat is one of Indonesian native goat that kept for meat and milk productions. This research was aimed to predict the growth curve of body weight in Ettawa crossbred goat at 1 - 24 months of age with Logistic (L) and Gompertz (G) mathematical models. The number of 48 goats (24 males and 24 females) were used in this study and collected from Tambang District, Kampar Regency, Riau Province of Indonesia. Research showed that L and G models have the very high coefficient determination (R2) value (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The results of this study showed that the body weights of male and female Kejobong individuals increased with age. This was in line with the finding of Putra et al (2022) that the body weight of young male Etawa Grade goats aged 8-12 months (30.42 ± 10.61 kg) was lower than that of adult male Etawa Grade goats aged 13-24 months (51.74 ± 2.94 kg). Similarly, the results of a study by Purnami et al (2021) showed that the body weight of male Kejobong goats aged 5 months (14.04±1.46 kg) was lower than that of male Kejobong goats aged 9 months (22.32±1.99 kg).…”
Section: Resultssupporting
confidence: 92%
“…The results of this study showed that the body weights of male and female Kejobong individuals increased with age. This was in line with the finding of Putra et al (2022) that the body weight of young male Etawa Grade goats aged 8-12 months (30.42 ± 10.61 kg) was lower than that of adult male Etawa Grade goats aged 13-24 months (51.74 ± 2.94 kg). Similarly, the results of a study by Purnami et al (2021) showed that the body weight of male Kejobong goats aged 5 months (14.04±1.46 kg) was lower than that of male Kejobong goats aged 9 months (22.32±1.99 kg).…”
Section: Resultssupporting
confidence: 92%